Magnetic Field-assisted Preparations for 1-D Carbon Nanomaterials: A Review. Issue 1786 (2015) - Luo, Chengzhi; Pan, Chunxu
ABSTRACT: One-dimensional carbon nanomaterials (1-DCNMs), as one of the most promising one-dimension nanomaterials due to its unique microstructure, peculiar chemical, mechanical, thermal, and electronic properties, have long been considered as an important building block to construct micro-nano-electrics and devices. The growth controllability in direction, morphology and microstructure may provide a straightforward platform for fabricating high performance 1-DCNMs-based devices. Recently, electric and magnetic fields have emerged as key techniques to control the 1-DCNMs' growth direction, morphology and microstructure. In this paper, we focus explicitly on the 1-DCNMs preparations with assistance of a magnetic field, and the main problems that should be solved in the future are also discussed.